Microcomputer System Organization for Evaluation of Microclimatic Elements in Environmental Areas - Kathijotes, Nicholas; Kolev, N. (My University, 2009)
This paper deals with an approach and methodology in the organization of measuring systems for the evaluation of microclimatic elements, for characterizing energy balance of the soil-vegetation-ground atmosphere in an area. Microcomputer systems for measurement and calculation of these climatic elements can be organized to use their full automated space distributed over large territories.
Keywords: Microclimate; Microcomputer; Energy balance; Ground atmosphere; Microclimate; Microcomputer; Energy balance; Ground atmosphere